Effects of culture mode and CO2 supply on the efficiency of Haematococcus pluvialis cultivation in recirculating aquaculture system’s wastewater - Rakib, Mazharul (2023)
Haematococcus pluvialis is a microalga that could be grown using wastewater (WW) from recirculating aquaculture systems (RAS) and by growing the alga in WW it is possible to trap the dissolved nutrients which otherwise would end up in the environment. Improvements in sustainability, resource efficiency, and the generation of a valuable carotenoid pigment (astaxanthin) may all result from converting wastewater nutrients into H. pluvialis biomass in RAS. In this master's thesis, I have done two experiments. In the first one, I examined the suitability of the culture mode by comparing the growth of H. pluvialis for 17 days in RAS WW under batch (input all the culture medium once) and fed-batch (input culture medium gradually) culture modes. In the second experiment of 15 days, I examined the algal growth and pH of the medium for 8 days until the microalga reach the stationary phase, nitrate removal (15 days), and astaxanthin concentration (on day 15) in Modified Wright's Cryptophyte (MWC) medium with batch culture mode by supplying air either from the RAS trickling filter where CO2 concentration was 964± 16.38 ppm or room air where CO2 was 451± 1.77 ppm. In the 1st experiment, the specific growth rate (SGR) (0.20±0.014 d-1) of the microalga culturing in batch culture mode was significantly higher than SGR (0.11±0.008 d-1) in fed-batch culture mode. In the second experiment, there was a statistically significant difference in cell density between the treatments (P=0.039) whereas in additional CO2 -treated culture had higher cell density. There was no significant difference in SGR between the treatments (RAS air = 0.27±0.017 d-1, room air = 0.25±0.006 d-1). On the other hand nitrate consumption rate was significantly higher in the RAS air treatment, i.e. with the additional CO2. The concentration of astaxanthin did not differ significantly between the treatments. Additional CO2 retained the medium's pH at a lower level and likely had a positive influence on algal growth and nutrient absorption. These results imply that the growth of H. pluvialis increased with the addition of CO2 from RAS in batch culture mode.